The Challenges of Collecting and Using Patient Care Data From Diverse Care Systems: Lessons From COMPASS. (September 2017) - Solberg, Leif I.; Ferguson, Robert; Ohnsorg, Kris A.; Crain, A. Lauren; Williams, Mark D.; Ziegenfuss, Jeanette Y.; Boggs, Jennifer M.; Neely, Claire; Brooks, Leslie; Molitor, Beth A.; Monkman, Jeyn; Coughlin, Meg
The ability to aggregate clinical data across multiple diverse organizations and to use it for performance measurement, quality improvement, evaluation, and research is rapidly becoming a national necessity, but there are few examples of how to do that. This article uses lessons from a national effort to implement the collaborative care management model for patients with both depression and diabetes or heart disease across 8 partner organizations, 18 medical groups, and more than 170 clinics in 8 states to identify the challenges and provide experience-based recommendations for those tasks. The challenges are divided into those needed for (1) collecting similar data, (2) aggregating those data across care systems, and (3) using the data to both improve and evaluate care. Start with agreement on goals, methods, transparency, and a data system integrated into the electronic medical record while promptly addressing all the legal, regulatory, and human subject requirements.